2007
DOI: 10.1371/journal.pone.0000194
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Exposure Incidents of the Health Care Personnel in a Newly Founded Tertiary Hospital: A Prospective Study

Abstract: BackgroundPercutaneous exposure incidents (PEIs) and blood splashes on the skin of health care workers are a major concern, since they expose susceptible employees to the risk of infectious diseases. We undertook this study in order to estimate the overall incidence of such injuries in a newly founded tertiary hospital, and to evaluate possible changes in their incidence over time.Methodology/Principal FindingsWe prospectively studied the PEIs and blood splashes on the skin of employees in a newly founded (Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
4
16
0
4
Order By: Relevance
“…Similarly to the observations by other researchers, both Polish and foreign [12][13][14][15], in our study nursing staff were the largest group after the exposure. This may be attributed to the fact that nurses are the largest occupational group among the HCWs [16].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to the observations by other researchers, both Polish and foreign [12][13][14][15], in our study nursing staff were the largest group after the exposure. This may be attributed to the fact that nurses are the largest occupational group among the HCWs [16].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, majority of NSIs were reported by staff nurses, (42.9%), which is a similar result compared with previous studies (4,6,(13)(14)(15)(16). This incidence rate is high though compared with a study done by Jayanth et al (17), where 28% of nurses had experienced NSIs.…”
Section: Discussionsupporting
confidence: 91%
“…Studies [18,19,20,21,22] conducted in health professionals in Brazil and other countries highlighted the nursing staff as the most injured during professional practice, with the greatest risk factor contact with sharps and potentially contaminated biological materials. Among the reasons given for greater vulnerability of nursing staff are the characteristics of the profession, as being the largest individual group of health professionals responsible for uninterrupted 24 hours a day service and perform a higher volume of direct patient care.…”
Section: Discussionmentioning
confidence: 99%